Seasonal and Spatial Variability of Biological N2 Fixation in a Cool Temperate Bog. Issue 2 (31st January 2022) - Živković, T.; Helbig, M.; Moore, T. R.
Abstract: Northern peatlands are globally important carbon (C) and nitrogen (N) sinks due to slow decomposition rates resulting in long‐term organic matter accumulation. Despite their large N storage, peatlands depend on sources of bio‐available N to sustain their biomass production. Di‐nitrogen (N2 ) fixation represents an important biological N source in ombrotrophic bogs, but its environmental controls are still poorly understood. We examined seasonal and spatial variability of Sphagnum ‐associated N2 fixation across a hydrological transect (hummock‐hollow‐beaver pond edge) in a temperate ombrotrophic bog. We measured N2 fixation in live Sphagnum plants by acetylene reduction assay calibrated with a 15 N2 tracer method, bi‐weekly, from May to November over two growing seasons. We found that N2 fixation increased with soil temperature at 5 cm in the living Sphagnum mat explaining the seasonal variability in N2 fixation. Peak N2 fixation rates occur in mid‐August, when N2 fixation rates are about 10 times larger than during the shoulder seasons (May and November). Spatially, N2 fixation was larger in wetter Sphagnum with larger gravimetric water content in Sphagnum . This relationship was most pronounced in the peak growing season when N2 fixation rates were the highest. Finally, we estimated that the Mer Bleue bog receives around 0.3 g N m −2 annually through Sphagnum ‐associated N2 fixation, which accounts for about a fourth of the N accumulated annually into Sphagnum . Future contributions from Sphagnum ‐associated N2 fixation to N budgets in peatlands will depend on temperature and moisture changes which have contrasting effects on N2 fixation rates. Plain Language Summary: Nitrogen is an important nutrient supporting plant growth. In rain‐fed peatlands (bogs), biological N2 fixation from atmospheric N2 represents an important N input to the ecosystem. There, Sphagnum mosses represent the dominant plant genus and host microbes capable of fixing nitrogen. Despite being an important source of nitrogen, the environmental controls on N2 fixation in bogs are still poorly understood. Here, we find that N2 fixation across the bog increases with temperature in Sphagnum throughout the growing season. Within the bog, areas of high N2 fixation are best characterized by high Sphagnum water content while areas of low N2 fixation are usually drier. N2 fixation most strongly follows these moisture patterns during the peak growing season when temperatures in Sphagnum reach their peak. In the fall and spring, when temperatures are cooler, these relationships become weaker. Our results show that both temperature and moisture in Sphagnum drive Sphagnum ‐associated N2 fixation in bogs. Our study helps us to better understand how N2 fixation and thus nutrient availability may change with a warming climate in nutrient‐poor bogs. Through its impact on plant growth, changes in nutrient availability have the potential to modify future long‐term carbon and nitrogen accumulation rates in these ecosystems. Key Points: N2 fixation in Sphagnum represents an important biological N source in ombrotrophic bogs Seasonal and spatial variability of N2 fixation was best explained by Sphagnum temperature and moisture, respectively Future Sphagnum ‐associated N2 fixation will depend on temperature and moisture changes which have contrasting effects